Chronic obstructive pulmonary disease in small animals - Gómez-Ortiz, Edna (2015)
Chronic obstructive pulmonary disease (COPD) is a disease of the lower airways, which result in remodelling of the pulmonary tract and culminates with narrowing airway causing progressive obstruction. The disease mainly affects elderly animals and the cause is generally unknown. This review aims to describe the clinical significance, diagnostic tools, main differences between the diagnosis of asthma and bronchitis, as well as therapeutic alternatives that offer better results and fewer side effects for patients.